2001
DOI: 10.1159/000055701
|View full text |Cite
|
Sign up to set email alerts
|

No Increased Serum Levels of Antifood Antibodies in Patients with Ménière’s Disease

Abstract: The etiology of Ménière’s disease (MD) is still unknown, but it is likely to be multifactorial, one of the factors being an immunological causation. Antifood allergens as well as anti-baker’s yeast antibodies are humoral factors that may be linked with allergenic disorders and other autoimmune conditions. To determine their possible role in MD activity, we investigated 29 MD sera for the presence of antibodies against gliadin, β-lactoglobulin, albumin, ovalbumin, soya, and Dermatophagoides pteronyssinus and Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The answer to our main question posed at the beginning of this work (“Is there a relationship between allergic diseases and inner ear disorders?”) is “yes.” All but two papers ( 49 , 57 ) found supportive evidence of a possible association between allergy and inner ear disorders. The backing evidence included an increased prevalence of allergic disorders (airborne or food allergies) in persons with MD, ISSHL, and ALHL ( 48 , 50–54 ) and an increased prevalence of inner ear disorders in AR patients ( 15 , 56 , 58 , 59 ) when compared to the control groups or general population.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The answer to our main question posed at the beginning of this work (“Is there a relationship between allergic diseases and inner ear disorders?”) is “yes.” All but two papers ( 49 , 57 ) found supportive evidence of a possible association between allergy and inner ear disorders. The backing evidence included an increased prevalence of allergic disorders (airborne or food allergies) in persons with MD, ISSHL, and ALHL ( 48 , 50–54 ) and an increased prevalence of inner ear disorders in AR patients ( 15 , 56 , 58 , 59 ) when compared to the control groups or general population.…”
Section: Discussionmentioning
confidence: 93%
“…Six studies (28.6%) included in this review investigated immune parameters in patients with inner ear disease ( Table 3 ). Boulassel et al ( 49 ), Keles et al ( 50 ), and Roomiani et al ( 55 ) focused on MD patients. Keles et al and Roomiani et al showed that MD patients had a higher concentration of total serum IgE than healthy subjects or patients with otologic disorders other than MD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Ménière's disease was described as long ago as 1860, it is still an obscure disease entity rather than a uniform disease and can be caused by a variety of etiological factors (4,9,10). Ménière's disease is often associated with the presence of EH, but the presence of EH does not exclude other etiologies.…”
Section: Introductionmentioning
confidence: 99%